PENGARUH PENDEKATAN SCIENTIFIC TERHADAP MOTIVASI DAN HASIL BELAJAR FISIKA SISWA - As’ad Furqon Syadzili; Sukainil Ahzan; Dwi pangga (Universitas Pendidikan Mandalika, 2015)
This research aimed to know there is or no effect of scientific approach toward student’s motivation and learning achievement. The kind of this research was experimental research. Design of this research used pretest and posttest one group design, with population was all students of XI IPA at SMAN 1 Kopang. Sample of this research consist of two classes that is class XI IPA 1 as experimental group and class XI IPA 2 as control group which used random sampling tachnique. Mean of pretest was 23,21 in experimental group and 30,15 in control group. Mean of posttest was 74,74 in experimental group and 57,68 in control group. Percentage of student’s learning motivation was increased 59,85% (low) in experimental group and 64,65% (quite) became 82,40% (high) in experimental group and 76, 56% (quite) in control group. The data of homogenity and normality was homogen and normal distribution. The data analysis used t-test. The result of t-test was 3,89 for motivation and 5,47 for learning achievement and t-table was 1,99 in 5% level of significant with t-test > t-table. This research showed that there is effect of scientific approach toward student’s motivation and learnig achievement at eleventh year students of SMAN 1 Kopang.